Evaluation of sheep sinonasal endoscopic anatomy as a model for rhinologic research. Issue 4 (1st December 2018) - Macias‐Valle, Luis; Finkelstein‐Kulka, Andres; Manji, Jamil; Okpaleke, Christopher; Al‐Salihi, Salahuddin; Javer, Amin R.
Abstract : Objectives: Despite many publications describing sheep models for functional endoscopic sinus surgery (FESS) procedures, accurate endoscopic anatomical studies are lacking. There are no publications correlating computed tomography (CT) and 3D models with endoscopic anatomical descriptions. This study evaluates and describes the endoscopic anatomy of a sheep model. Methods: Ten live sheep (20‐sides) were included. Two cadaveric specimens, imaged using thin slice CT for 3D reconstruction correlation were also included. Using endoscopy, anatomical structures were measured and described. Measurement of the same structures was carried out using the 3D imaging model. Results: Three sets of turbinates were identified at 2.3, 5.1 and 8.5 cm from the anterior nasal sill. Frontal recess and uncinate process were identified at 12.7 cm. The septum has a bony and cartilaginous component and measures 10.5 cm. The sphenopalatine foramen was measured at 12.1 cm. All anatomical measurements were correlated with the measurements on the CT scan 3D volume‐rendering model, thereby allowing for an accurate description of the sheep sinonasal anatomy. Conclusion: This study describes the endoscopic sinonasal anatomical measurements of the adult sheep. It is the first study to evaluate the sheep CT and endoscopic anatomy in order to determine its feasibility as an animal model for research in FESS.